Esculetin Ameliorates Psoriasis-Like Skin Disease in Mice by Inducing CD4+Foxp3+ Regulatory T Cells - Chen, Yuchao; Zhang, Qunfang; Liu, Huazhen; Lu, Chuanjian; Liang, Chun-Ling; Qiu, Feifei; Han, Ling; Dai, Zhenhua (Frontiers in Immunology, 2018)
Psoriasis is an autoimmune and inflammatory skin disease affecting around 2-3% of the world’s population. Patients with psoriasis need extensive treatments with global immunosuppressive agents that may cause severe side effects. Esculetin, a type of coumarins, is an active ingredient extracted mainly from the bark of Fraxinus rhynchophylla, which has been used to treat inflammatory and autoimmune diseases in China. However, the antipsoriatic effects of esculetin have not been reported. In this study, we aimed to investigate the effects of esculetin on psoriatic skin inflammation in a mouse model and explored the potential molecular mechanisms underlying its action. We found that esculetin ameliorated the skin lesion and reduced PASI scores as well as weight loss in imiquimod-induced psoriasis-like mice, accompanied with weakened proliferation and differentiation of keratinocytes and CD3+ T cell infiltration in esculetin-treated psoriatic mice. In addition, esculetin reduced the frequency of CD8+CD44highCD62Llow effector T cells in psoriatic mice. In contrast, it increased the frequency of CD4+Foxp3+ Tregs in both lymph nodes and spleens of the psoriatic mice while promoting the differentiation of CD4+CD25- T cells into CD4+Foxp3+ Tregs in vitro. Interestingly, depleting CD4+Foxp3+ Tregs largely reversed esculetin-mediated reduction in PASI scores, indicating that esculetin attenuates murine psoriasis mainly by inducing CD4+Foxp3+ Tregs. Furthermore, the mRNA levels of proinflammatory cytokines in the psoriatic mouse skin, including IL-6, IL-17A, IL-22, IL-23, TNF-α and IFN-γ, were dramatically decreased by the treatment with esculetin. Finally, we found that esculetin inhibited the phosphorylation of IKKα and P65 in the psoriatic skin, suggesting that it inhibits the activation of NF-κB signaling. Thus, we have demonstrated that esculetin attenuates the psoriasis-like skin lesion in mice and may be a potential therapeutic candidate for the treatment of psoriasis in clinic.